Nothing Ever Ends: Critical Race Theory, Schwarzer Humanismus und Watchmen - Hartmann, Alexandra (Alle Uns: Differenz, Identität, Repräsentation)

Validation of the student version of the Perceptions of Inclusion Questionnaire in primary and secondary education settings - Knickenberg, Margarita; Zurbriggen, Carmen L. A.; Schwab, Susanne (SAGE Open)
Considering students’ voices and perspectives is indispensable in educational contexts. Therefore, instruments of measurement that are reliable and valid and can be used easily without complications are needed in schools. The Perceptions of Inclusion Questionnaire (PIQ) is a short instrument used to assess three central dimensions of inclusion, namely emotional and social inclusion and academic self-concept. Previous evaluations indicate in general high psychometric properties. This study aimed to evaluate the construct validity of the three scales of the PIQ’s student version using different approaches in two samples from primary (grade 4, N = 721) and secondary (grade 7, N = 393) schools. The results of confirmatory factorial analyses confirmed the PIQ’s three factors in both samples which are also measurement equivalent across grades. Plausible correlations with additional divergent and convergent scales reveal that the PIQ measures the theoretically assumed constructs—emotional and social inclusion as well as academic self-concept—validly.
Keywords: General Social Sciences; General Arts and Humanities

Recht und Wirtschaft in Europa, Bd. 1: Lüke: Reverse Factoring - Eine rechtliche und ökonomische Analyse - Krimphove, Dieter

Internationale Schiedgerichtsbarkeit: Perspektiven für die Wirtschaft - Krimphove, Dieter

MaRisk: Kommentar: Rundschreiben 10/2021 (BA) - Mindestanforderung an das Risikomanagement - Krimphove, Dieter; Lüke, Christoph

Völkerrecht und IPR - Krimphove, Dieter; Lentner, Gabriel

Kapitalmarktrecht - Krimphove, Dieter; Lüke, Christoph

Brave New Kachel-World? Über Zoom-Booming, Datenkontrolle und öffentliche Infrastrukturen - Weber, Jutta (Von Menschen und Maschinen – Mensch-Maschine-Interaktionen in digitalen Kulturen)

Ende des werberechtlichen Schattendaseins der "Hörmarke" - Zugleich eine Analyse von EuG "Ardagh Metal Beverage/EUIPO" - Krimphove, Dieter (Zeitschrift für Gewerblichen Rechtsschutz und Urheberrecht)

Die Körordnung im deutschen und Europäischen Recht - Krimphove, Dieter; Schlief, Till (Natur und Recht NuR)

Mehr Geld ohne Mehrarbeit? - Krimphove, Dieter (ArbR - Arbeitsrecht Aktuell)

Geldwäsche: Tatbestände, Aufgriffsmöglichkeiten, Indizien im Zahlungs- und Kapitalmarkt - Krimphove, Dieter; Ikemeyer, Raphael (Compliance Berater)

Der EuGH und die Rechtsstaatlichkeit Polens - Anmerkung zum Urteil des EuG v. 9.2.2922, Rs. T-791/19 (Sped-Pro) - Krimphove, Dieter (Europarecht)

Neobanken - Regelungslücke im Aufsichtsrecht? - Krimphove, Dieter; Knoblich, René (Compliance Berater)

Der EuGH und der ersatzlose Verfall des Jahresurlaubes - Krimphove, Dieter (ArbR - Arbeitsrecht Aktuell)

Cross-Compliance im Umweltschutz und Landwirtschaft - Krimphove, Dieter (Natur und Recht)

Schlussbericht ITS.ML: Intelligente Technische Systeme der nächsten Generation durch Maschinelles Lernen. Forschungsvorhaben zur automatisierten Analyse von Daten mittels Maschinellen Lernens - Hammer, Barbara; Hüllermeier, Eyke; Lohweg, Volker; Schneider, Alexander; Schenck, Wolfram; Kuhl, Ulrike; Braun, Marco; Pfeifer, Anton; Holst, Christoph-Alexander; Schmidt, Malte; Schomaker, Gunnar; Tornede, Tanja

Light Scattering by Large Densely Packed Clusters of Particles - Grynko, Yevgen; Shkuratov, Yuriy; Alhaddad, Samer; Förstner, Jens (Springer Series in Light Scattering - Volume 8: Light Polarization and Multiple Scattering in Turbid Media)
We review our results of numerical simulations of light scattering from different systems of densely packed irregular particles. We consider spherical clusters, thick layers and monolayers with realistic topologies and dimensions much larger than the wavelength of light. The maximum bulk packing density of clusters is 0.5. A numerically exact solution of the electromagnetic problem is obtained using the Discontinuous Galerkin Time Domain method and with application of high- performance computing. We show that high packing density causes light localization in such structures which makes an impact on the opposition phenomena: backscattering intensity surge and negative linear polarization feature. Diffuse multiple scattering is significantly reduced in the case of non-absorbing particles and near-field interaction results in a percolation-like light transport determined by the topology of the medium. With this the negative polarization feature caused by single scattering gets enhanced if compared to lower density samples. We also confirm coherent double scattering mechanism of negative polarization for light scattered from dense absorbing slabs. In this case convergent result for the scattering angle polarization dependency at backscattering can be obtained for a layer of just a few tens of particles if they are larger than the wavelength.
Keywords: tet_topic_scattering

Schnittstellenaufgaben in der Analysis I zur Verknüpfung von Schul- und Hochschulmathematik - Aufgabenbeispiele und Ergebnisse einer Evaluationsstudie. - Hoffmann, Max; Biehler, Rolf (Bedarfsgerechte fachmathematische Lehramtsausbildung. Analyse, Zielsetzungen und Konzepte unter heterogenen Voraussetzungen)

Fachwissen als Grundlage fachdidaktischer Urteilskompetenz – Beispiele für die Herstellung konzeptueller Bezüge zwischen fachwissenschaftlicher und fachdidaktischer Lehre im gymnasialen Lehramtsstudium - Biehler, Rolf; Hoffmann, Max (Professionsorientierte Fachwissenschaft. Kohärenzstiftende Lerngelegenheiten für das Lehramtsstudium Mathematik)

Formen, Ziele und Probleme der Eroberungspolitik im Mittelalter. Eine Einführung - Kamp, Hermann (Herrschaft über Fremde Völker und Reiche. Formen, Ziele und Probleme der Eroberungspolitik im Mittelalter)

Herrschaft über Fremde Völker und Reiche. Formen, Ziele und Probleme der Eroberungspolitik im Mittelalter

Probably Approximately Correct. Epistemologische Grundlagen der Künstlichen Intelligenz - Weber, Jutta (Mensch-Maschine-Interaktion – Konzeptionelle, soziale und ethische Implikationen neuer Mensch-Technik-Verhältnisse)

iMustHave. Anhand von Werbevideos den Kult um den digital global player Apple untersuchen - Hohwiller, Peter; Bauer, Maike (Der fremdsprachliche Unterricht Englisch)

Lehrplan Englisch für die Sekundarstufe I in Rheinland-Pfalz - Hohwiller, Peter; Brünker, Peter; Ritzenhofen, Ute; Kammer, Dorit

Information Leaks and Voluntary Disclosure - Ebert, Michael; Schäfer, Ulrich; Schneider, Georg Thomas

Development of Simulation Based Assistant Systems for Automatic Process Monitoring and Derivation of Recommendations to Optimize a Profile Extrusion Line - Schöppner, Volker; Köllermeier, Jonas; Hiesgen, G.; Trippe, J.

Application of a Dynamic Approach to Determine the Optimal Barrel Temperature of Single Screw Extruders - Schöppner, Volker; Köllermeier, Jonas

Development of an Inline-Measurement System of the Surface Temperature of Square Hollow Profiles - Schöppner, Volker; Köllermeier, Jonas

HOMOGENIZATION OF TWIN-ROLL CAST Al-Li-BASED ALLOY STUDIED BY IN-SITU ELECTRON MICROSCOPY - CIESLAR, Miroslav; KŘIVSKÁ, Barbora; KRÁLÍK, Rostislav; BAJTOŠOVÁ, Lucia; Grydin, Olexandr; STOLBCHENKO, Mykhailo; Schaper, Mirko (METAL 2022 Conference Proeedings)
Transformation of Fe- and Cu-rich primary phase particles was studied in an Al-Li-based alloy prepared by twin-roll casting. Thin foils for combined STEM and SEM experiments were prepared by electrolytic twin-jet polishing. They were in-situ heated in a TEM heating stage and observed at 200 kV in the JEOL JEM 2200FS electron microscope equipped with STEM HAADF and BF detectors and SEM BSE and SE detectors working both in composition and topographic modes. The resulting structures were combined with EDS mapping performed directly in the heating holder. Dissolution and transformation of Cu- and Fe-rich particles occur above 500 °C. EDS maps acquired on the foil cooled down to room temperature show that Cu and Fe are both still present in newly formed particles, most likely indicating the presence of the Al7Cu2Fe phase.
Keywords: Al-Li-based alloy; in-situ TEM; homogenization; phase transformation

Du Châtelet and Kant: Claiming the Renewal of Philosophy - Hagengruber, Ruth Edith (Époque Émilienne)
n 1789, Eberhard repudiated Kant’s claim expressed in the first edition of his Critique of Pure Reason to have delivered a new, namely transcendental turn in philosophy, as he was able to retrace our cognition to the origin of phenomena instead of delivering a “merely logical deduction”. Eberhard holds that there was nothing new, but all delivered in Leibniz and Wolff; to prove his claim he refers to a quote from Du Châtelet, taken from a paragraph where she determines the right understanding as to be able “to penetrate to the origin of phenomena”. This paper brings Du Châtelet into discourse with Kant via this Eberhard quote. In its first part, it investigates the use of her quote in the Kant-Eberhard controversy. The second part serves to ground the quote in Du Châtelet’s epistemology. It lays out how to understand Du Châtelet’s claim to penetrate to the origin of phenomena. Du Châtelet’s claim to have renewed philosophy must be taken seriously, and it is helpful for rethinking the German philosophical development from the rationalists to Kant through including Du Châtelet’s theory of cognition.
Keywords: Émilie Du Châtelet; History of Science; Newton; Kant; Eberhard; Wolff; Leibniz

Époque Émilienne
Keywords: Émilie Du Châtelet; History of Science; Kant; Newton; Maupertuis; Voltaire

Tilting nondispersive bands in an empty microcavity - Gao, Ying; Li, Yao; Ma, Xuekai; Gao, Meini; Dai, Haitao; Schumacher, Stefan; Gao, Tingge (Applied Physics Letters)
Recently, microcavities with anisotropic materials were shown to be able to create bands with non-zero local Berry curvature. The anisotropic refractive index of the cavity layer is believed to be critical in opening an energy gap at the tilted Dirac points. In this work, we show that the anticrossing between a cavity mode and a Bragg mode can also be realized within an empty microcavity without any birefringent materials in the cavity layer. Nondispersive bands are observed within the energy gap due to the particular refractive index distribution of the sample. The intrinsic TE-TM splitting and XY splitting of DBR mirrors induce the squeezing of the cavity modes in momentum space, so that the nondispersive bands are tilted and spin-dependent. Our results pave the way to investigate interesting physical phenomena of photonic modes close to or in the nondispersive bands without anisotropic cavity layers.
Keywords: Physics and Astronomy (miscellaneous)

Funnel PMC with feasibility constraints for nonlinear systems with arbitrary relative degree - Berger, Thomas; Dennstädt, Dario (IEEE Control Systems Letters)

Feedback control of the COVID-19 pandemic with guaranteed non-exceeding ICU capacity - Berger, Thomas (Systems & Control Letters)

Partial impulse observability of linear descriptor systems - Jaiswal, J.; Berger, Thomas; Tomar, N. K. (Systems & Control Letters)

Funnel control for a moving water tank - Berger, Thomas; Puche, M.; Schwenninger, F. L. (Automatica)

On an extension of a global implicit function theorem - Berger, Thomas; Haller, F. (Comptes Rendus Mathématique)

Der Fall Coca Cola - "Arbeitsverweigerung" des EuGH? - Krimphove, Dieter (ArbR- Arbeitsrecht Aktuell)

Information extraction in photon-counting experiments - Schapeler, Timon; Bartley, Tim (Physical Review A)

Laser-lithographically written micron-wide superconducting nanowire single-photon detectors - Protte, Maximilian; Verma, Varun B; Höpker, Jan Philipp; Mirin, Richard P; Woo Nam, Sae; Bartley, Tim (Superconductor Science and Technology)
Abstract We demonstrate the fabrication of micron-wide tungsten silicide superconducting nanowire single-photon detectors on a silicon substrate using laser lithography. We show saturated internal detection efficiencies with wire widths ranging from 0.59 µ m to 1.43 µ m under illumination at 1550 nm. We demonstrate both straight wires, as well as meandered structures. Single-photon sensitivity is shown in devices up to 4 mm in length. Laser-lithographically written devices allow for fast and easy structuring of large areas while maintaining a saturated internal efficiency for wire widths around 1 µ m.
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Metals and Alloys; Condensed Matter Physics; Ceramics and Composites

Cryogenic integrated spontaneous parametric down-conversion - Lange, Nina Amelie; Höpker, Jan Philipp; Ricken, Raimund; Quiring, Viktor; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Optica)
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Tagungsbericht: Unverfügbarkeit – Widmung – Latenz: Das Heilige in der Kultur. Interdisziplinäre Tagung vom 16. bis 18. November 2021 an der Universität Paderborn - Becker, Rieke; Lauert, Markus; Fischer, Jessica; Kirchhoff, Hannah; Kornbach, Alina; Januschewski, Katharina

Experimental Measurement Method and Evaluation of an Analytical Approach for Sound Conduction through Multiple Clinched Sheets - Stephan, Richard; Brosius, Alexander (The 28th Saxon Conference on Forming Technology SFU and the 7th International Conference on Accuracy in Forming Technology ICAFT)
The conduction of structure-borne sound through joints causes energy dissipation. The sound reduction index describes this energy loss as a level decrease in the particle velocity across series-connected damping elements for which the superposition principle applies. This simple model can help to develop a testing method for joints based on this characteristic energy loss. In this paper, this model is experimentally evaluated for multiple in-series clinched aluminium sheets. Samples connected by several clinch points arranged in parallel are investigated experimentally, and the results are discussed.
Keywords: clinching; mechanical joining; damping; model; evaluation; dynamics

Experimental and Numerical Investigation on Manufacturing-Induced Pre-Strain on the Load-Bearing Capacity of Clinched Joints - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (Key Engineering Materials)
Background. Clinching is a conventional cold forming process in which two or more sheets can be joined without auxiliary parts. A pre-forming of the parts to be joined, which is introduced by previous manufacturing steps, has an influence on the joining result. When considering the suitability for joining with regard to the formability of the materials, the influence of the preforming steps must be taken into account. The influences of strain hardening and sheet thickness on the joining properties must be investigated. In this context, a Finite Element Method (FEM) based metamodel analysis of the clinching process was carried out in [1] to investigate the robustness of the clinching process with respect to the different material pre-strains. In [2], the method was extended to the load bearing simulation.Procedure. The metamodel from preliminary work based on various FE models, which predicts the load-bearing capacity of a clinched joint influenced by pre-straining, is compared here with experimental data and the accuracy of the metamodel prediction is discussed. For this purpose an experimental procedure was further develop which allows the preforming of metal sheets from which joining specimens can be separated with a certain degree of unidirectional deformation. In the study, the procedure for preparing the joint specimens and the results of the loading tests are presented. Different possible relevant pre-strain combinations are investigated and compared with the simulation results, to validate the FE models and choose suitable metamodel.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Experimental and Numerical Analysis of Cold Formed Multi Pin Structures Using a Multi-Acting Tool Design - Römisch, David; Merklein, Marion

Versatile tool design for a tumbling self-piercing riveting process - Wituschek, Simon; Lechner, Michael

Approach to Determine the Characteristic Dimensions of Clinched Joints by Industrial X-ray Computed Tomography - Busch, Matthias; Köhler, Daniel; Hausotte, Tino; Kupfer, Robert; Troschitz, Juliane; Gude, Maik
Destructive micrograph analysis (MA) is the standard method for the assessment of clinched joints. However, during the joint preparation for the MA, geometric features of the joint can change due to elastic effects and closing cracks. X-ray computed tomography (CT) is a promising alternative to investigate the joint non-destructively. However, if the material properties of similar joining partners are the same, the CT is not able to correctly resolve surfaces in the joint that are close to or pressing onto each other. These surfaces are relevant for the determination of characteristic dimensions such as neck thickness and undercut. By placing a thin, highly radiopaque tin layer between the joining partners, the interfacial area in the reconstructed volume can be highlighted. In this work, a method for the localisation of the tin layer inside the joint as well as threshold value procedures for the outer joint contour in cross section images are investigated. The measured characteristic dimensions are compared with measured values from MA of the same samples and of samples without tin layer. In addition, possible effects of the tin layer on the joining point characteristics as well as problems of the MA are discussed.

Cryogenic electro-optic modulation in titanium in-diffused lithium niobate waveguides - Thiele, Frederik; vom Bruch, Felix; Brockmeier, Julian; Protte, Maximilian; Hummel, Thomas; Ricken, Raimund; Quiring, Viktor; Lengeling, Sebastian; Herrmann, Harald; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Journal of Physics: Photonics)
Abstract Lithium niobate is a promising platform for integrated quantum optics. In this platform, we aim to efficiently manipulate and detect quantum states by combining superconducting single photon detectors and modulators. The cryogenic operation of a superconducting single photon detector dictates the optimisation of the electro-optic modulators under the same operating conditions. To that end, we characterise a phase modulator, directional coupler, and polarisation converter at both ambient and cryogenic temperatures. The operation voltage <?CDATA $V_{π/2}$?> V π / 2 of these modulators increases, due to the decrease in the electro-optic effect, by 74% for the phase modulator, 84% for the directional coupler and 35% for the polarisation converter below 8.5 <?CDATA $\,K$?> K . The phase modulator preserves its broadband nature and modulates light in the characterised wavelength range. The unbiased bar state of the directional coupler changed by a wavelength shift of 85 <?CDATA $\,nm$?> n m while cooling the device down to 5 <?CDATA $\,K$?> K . The polarisation converter uses periodic poling to phasematch the two orthogonal polarisations. The phasematched wavelength of the utilised poling changes by 112 <?CDATA $\,nm$?> n m when cooling to 5 <?CDATA $\,K$?> K .
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Opto-electronic bias of a superconducting nanowire single photon detector using a cryogenic photodiode - Thiele, Frederik; Hummel, Thomas; Protte, Maximilian; Bartley, Tim (APL Photonics)
Superconducting Nanowire Single Photon Detectors (SNSPDs) have become an integral part of quantum optics in recent years because of their high performance in single photon detection. We present a method to replace the electrical input by supplying the required bias current via the photocurrent of a photodiode situated on the cold stage of the cryostat. Light is guided to the bias photodiode through an optical fiber, which enables a lower thermal conduction and galvanic isolation between room temperature and the cold stage. We show that an off-the-shelf InGaAs–InP photodiode exhibits a responsivity of at least 0.55 A/W at 0.8 K. Using this device to bias an SNSPD, we characterize the count rate dependent on the optical power incident on the photodiode. This configuration of the SNSPD and photodiode shows an expected plateau in the single photon count rate with an optical bias power on the photodiode above 6.8 µW. Furthermore, we compare the same detector under both optical and electrical bias, and show there is no significant changes in performance. This has the advantage of avoiding an electrical input cable, which reduces the latent heat load by a factor of 100 and, in principle, allows for low loss RF current supply at the cold stage.
Keywords: Computer Networks and Communications; Atomic and Molecular Physics; and Optics